Analysis of Phytotelmata As Breeding Site Aedes spp. in Sidoarjo East Java - Fita Fitriatul Wahidah; Rosmanida (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Dengue hemorrhagic fever (DHF) is a disease that is a problem in Indonesia, especially East Java. Sidoarjo is one of the city with high DHF cases in East Java with a total cases until 1,708 in 2016. One of the factors that support the increase in DHF cases is the availability of breeding site of Aedes. Research about breeding sites of Aedes in plants is limited. Vector control is often carried out only to ponds, air containers, and other artificial breeding sites, while in nature there are many plants that can to used breeding site such as phytotelmata. Phytotelmata are plants that can hold water in one of their bodies. This study aimed to determine the diversity of types and types of phytothelium, the physical condition of the water collected in the phytothelium and the Aedes species found in the phytotelmata. This research used descriptive observational. Determination of the sampling point using purposive sampling method. The results showed that there were eight species of phytotelmata which were used as breeding site for Aedes spp. in Sidoarjo, namely Musa paradisiaca, Pandanus amaryllifolius, Cocos nucifera, Neoregelia spectabilis, Bambusa sp. Neoregelia charm, Aechmea fasciata, and Xanthosoma sagittifolium. The Aedes species found were mostly Ae. albopictus. The average of air volume of the phytotelmata is 95.84 ml with water temperatures is 25-26oC and water pH is 6-7.